2022
DOI: 10.3389/fpsyt.2021.696544
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Myocardial Infarction as a Function of Temperamental Traits, Stress Coping Styles, and Posttraumatic Stress Disorder Symptoms

Abstract: The presented study aims to explore the relationship between quality of life after myocardial infarction and factors such as temperamental traits, stress coping, and posttraumatic stress disorder (PTSD) symptoms. Ninety-six participants, including 51 females and 45 males aged 24–85 years, who have survived ST-elevation myocardial infarction were asked to complete the Formal Characteristics of Behavior—Temperament Inventory, Coping Inventory for Stressful Situations, PTSD Inventory, and Quality of Life SF-36 qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For example, Chung et al (2008) found that people who used emotion-focused or avoidant coping strategies were more likely to report PTSS and other symptoms of psychological distress after MI. Several other studies confirmed this finding (Ayers et al, 2009;Marke and Bennett, 2013;Burnos and Wrzosek, 2022). On the other hand, high task-oriented coping has been associated with lower depression scores and more favorable illness attitude in patients with ACS (Wrześniewski et al, 1994;Messerli-Bürgy et al, 2015).…”
Section: Introductionmentioning
confidence: 77%
“…For example, Chung et al (2008) found that people who used emotion-focused or avoidant coping strategies were more likely to report PTSS and other symptoms of psychological distress after MI. Several other studies confirmed this finding (Ayers et al, 2009;Marke and Bennett, 2013;Burnos and Wrzosek, 2022). On the other hand, high task-oriented coping has been associated with lower depression scores and more favorable illness attitude in patients with ACS (Wrześniewski et al, 1994;Messerli-Bürgy et al, 2015).…”
Section: Introductionmentioning
confidence: 77%